To study the Erosion Behavior of H.V.O.F. Coating of 16Cr5Ni at the Different Velocity of Slurry - Umakant Yadav; Naresh Kumar; Mukesh Kumar Rathi (International Journal of Advances in Applied Sciences, 2014)
This paper describes erosion characteristics of high velocity oxy fuel (H.V.O.F.) along with commonly used steels 16Cr5Ni in Turbine and studied the comparison the effect of erosion at Different Velocities of the slurry on Cr2O3 and CrC-NiCr coating on steel. The four different ranges of velocity is taken i.e. 35m/s, 50m/s ,60and 70m/s. at normal impact angle and comparison regarding the erosion resistance was determined from the mass loss results. Higher erosion takes place at medium range of velocity i.e. at 50 m/s. Based on this experimental study coating was considered acceptable for the processes employed